2013
DOI: 10.5539/ass.v9n12p79
|View full text |Cite
|
Sign up to set email alerts
|

Family Business Succession of SMEs and Post-Transition Business Performance

Abstract: This study aimed at identifying the relationship between the success factors of succession in terms of preparation of heirs, the relationship between family and business as well as planning and control activities to smooth transition process. In addition, the smoothness of the transition process was also studied to determine its relationship with post-transition performance. This study included 70 of the successors of family business around Kuala Terengganu which are selected as study samples. Data was analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 42 publications
(44 reference statements)
1
26
0
3
Order By: Relevance
“…Ineffective succession process has serious implications, not only for the family members and business partners, but also for the country's economic development (Buang et al, 2013). Kim and Gao (2012) identified that the interaction between family, business, and family members creates systemic conditions and constituencies that affect the performance of the family business in the long run (Kim and Gao, 2012).…”
Section: Relationship Between the Succession And The Success Of A Fammentioning
confidence: 99%
See 3 more Smart Citations
“…Ineffective succession process has serious implications, not only for the family members and business partners, but also for the country's economic development (Buang et al, 2013). Kim and Gao (2012) identified that the interaction between family, business, and family members creates systemic conditions and constituencies that affect the performance of the family business in the long run (Kim and Gao, 2012).…”
Section: Relationship Between the Succession And The Success Of A Fammentioning
confidence: 99%
“…An effective process of succession is crucial in determining the continuity of the family business (Buang et al, 2013;Carlock & Ward, 2005) and problems related to succession becomes the key factor and continue to be a threat towards the success and the continuity of the family business (Brenes et al, 2011;Buang et al, 2013;Norita et al, 2010). According to Carlock and Ward (2005), planning a succession is about pooling talented people who can contribute their special skills and abilities towards the business' success, by trying to achieve the company's short-term and long-term goals.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Family businesses have dominated the economic landscape around the world (Liu, Yang &Zhang, 2010 andWee &Ibrahim, 2012), contribute an average of 75% of the GDP (Prior, 2012 andBuang, Ganefri &Sidek, 2013) and are widely seen as the backbone of the economy (Schwass, 2013). Family businesses, particularly the small-to-medium sized, are the grassroots of the global economy (Wallace, 2010), and are clearly the majority of all the businesses in the world (Buang et al, 2013). By their very nature, most SMEs are family businesses (Maalu, MacCormick, K"Obobyo & Machuki, 2013).…”
Section: Introductionmentioning
confidence: 99%